Gender differences in adaptive strategies of the population of the Republic of Tuva - Natsak, Organa D.; Balakina, Galina F. (The New Research of Tuva, 2024)
The article analyzes gender differences in the adaptive strategies of the population of the Republic of Tuva in terms of choosing ways to improve their financial situation. It also examines the propensity and interest of the population in traditional occupations and migration intentions, based on the results of a recent sociological survey conducted in 2023 among the population of Tuva (sample is 421). The study found that Tuvan women tend to be more socially active than men. In order to increase their family income, they often choose optimal strategies such as obtaining additional education or changing their profession. They are more willing to take risks, seek to avoid being limited to a fixed income, and search for new market niches to increase their income. In the adaptive strategies of the population in the Republic of Tuva, a general trend has been identified that is related to the desire for well-paid urban jobs and migration outside the republic. Women show less interest in traditional Tuvan occupations as a professional activity and adaptive strategy, and a greater propensity for market-related activities and entrepreneurship than men. Tuvan women are more focused on innovative activities. An analysis of respondents’ migration intentions revealed that women of Tuva prefer interregional migration over intraregional migration. The motives for migration intentions include the desire to find a better-paid job, a promotion, to provide their children with a higher level of education, and to be reunited with relatives.